Accuracy assessment of PACS workstation monitor measurements compared to real-time ultrasound imaging of abdominal organs - Mohammed Alsaadi; Salman Alomaireenie; Tariq Abd Al-Sattar; Mohsen Alshaibani; Abdulrahman Alfuraih (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Accurate anatomical measurements obtained using ultrasound (US) are crucial for diagnosis and informed clinical decision-making. Radiological display monitors integrated with Picture Archiving and Communication Systems (PACS) are commonly employed for post-acquisition analysis; however, the accuracy of PACS-derived measurements compared to real-time US remains underexplored. This study aims to assess the degree of agreement and reliability between real-time US and PACS-based measurements of abdominal organs. Methods A prospective analysis was conducted on 404 US images, including 101 each of the liver, spleen, right kidney, and left kidney. Two experienced sonographers obtained real-time measurements using a Logiq E10 system. Two radiologists, blinded to the original data, performed PACS measurements independently. Statistical analyses included paired t-tests, Pearson correlation coefficients, Bland–Altman plots, and intraclass correlation coefficients (ICC). Results Statistically significant differences (p < 0.001) were found between real-time and PACS measurements for all organs. Mean discrepancies ranged from 0.094 cm (left kidney) to 0.269 cm (liver). Pearson correlation coefficients varied from 0.888 to 0.994, indicating strong linear associations. Bland–Altman analysis demonstrated acceptable agreement, with limits within ± 0.74 cm, except for the liver. ICC values (0.886–0.994) confirmed high inter-method reliability. Conclusion Despite significant differences, a strong correlation and high reliability suggest that PACS-derived measurements may be clinically interchangeable with real-time US in most cases. These findings underscore the importance of standardising measurement protocols and enhancing training to ensure consistency and precision across imaging modalities.